2016
DOI: 10.1115/1.4033673
|View full text |Cite
|
Sign up to set email alerts
|

Neuromusculoskeletal Model Calibration Significantly Affects Predicted Knee Contact Forces for Walking

Abstract: Though walking impairments are prevalent in society, clinical treatments are often ineffective at restoring lost function. For this reason, researchers have begun to explore the use of patient-specific computational walking models to develop more effective treatments. However, the accuracy with which models can predict internal body forces in muscles and across joints depends on how well relevant model parameter values can be calibrated for the patient. This study investigated how knowledge of internal knee co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 50 publications
2
48
1
Order By: Relevance
“…This is understandable, as implant patients are discouraged from performing such vigorous tasks due to risks to the implant. However model predictions have been consistent with previous literature (Fregly et al, 2012;Fregly et al, 2009), where comparisons were possible, we have shown accurate predictions of joint moments (Lloyd and Besier, 2003) and TFJ contact loads (Gerus et al, 2013;Serrancoli et al, 2016;Walter et al, 2014;Wu et al, 2016).…”
Section: Resultssupporting
confidence: 90%
“…This is understandable, as implant patients are discouraged from performing such vigorous tasks due to risks to the implant. However model predictions have been consistent with previous literature (Fregly et al, 2012;Fregly et al, 2009), where comparisons were possible, we have shown accurate predictions of joint moments (Lloyd and Besier, 2003) and TFJ contact loads (Gerus et al, 2013;Serrancoli et al, 2016;Walter et al, 2014;Wu et al, 2016).…”
Section: Resultssupporting
confidence: 90%
“…Previous studies involving people with instrumented knee implants (Fregly et al, 2012) have also shown that calibrating the NMS model to the individual is essential in estimating accurate KJCF (Gerus et al, 2013;Serrancolí et al, 2016). Furthermore, tracking experimental KJCF measurements (Serrancolí et al, 2016) or minimising peak KJCF (Gerus et al, 2013) were additional calibration criteria that successfully improved KJCF estimates.…”
Section: Discussionmentioning
confidence: 99%
“…However, muscle excitations predicted by the 5 synergy excitations were only slightly closer to the 13 experimental muscle excitations than were those predicted by the 44 independent muscle excitations. Serrancol ı et al [35] found 44 muscle excitations that could be closely fit by 5 synergy excitations derived from ten experimental muscle EMG signals collected from a different instrumented knee subject. Neuromusculoskeletal model parameter values were calibrated using a two-level optimization approach, and the calibrated model predicted knee contact and leg muscle forces for walking trials withheld from the calibration process.…”
Section: Heuristic #4mentioning
confidence: 99%
“…Transactions of the ASME Refs. [27,35]). If the unknown synergy excitations could be obtained from experimentally measured muscle excitations, they could serve as subject-specific basis functions to constrain and simplify the construction of all muscle excitations [26].…”
Section: -6 / Vol 140 January 2018mentioning
confidence: 99%